The Role of Independent Commissioners in Realizing The Principles of Good Corporate Governance - Apriliani, Desi (Universitas Muhammadiyah Surakarta, 2023)
The existence of independent commissioners is intended to create a more objective, independent climate, as well as to maintain fairness and provide a balance between the interests of majority shareholders and the protection of the interests of minority shareholders, even other interests. Independent Commissioners are needed by companies in Indonesia, especially for public companies. With the existence of independent commissioners, all interested parties benefit greatly, especially through the establishment of conditions in accordance with the principles of Good Corporate Governance, where independent commissioners can provide opinions with a higher level of independence and accountability.